2007
DOI: 10.1002/pen.20768
|View full text |Cite
|
Sign up to set email alerts
|

Wood flour filled polypropylene composites: Interfacial adhesion and micromechanical deformations

Abstract: Polypropylene/wood flour composites were prepared in a wide composition range from 0 to 80 wt% filler content. The adhesion of the components was modified by two maleic anhydride functionalized polypropylenes (MAPP) with different maleic anhydride content and molecular weight. The components were homogenized in an internal mixer and then compression molded to 4 mm thick plates. Tensile properties were measured and micromechanical deformation processes were followed by acoustic emission as well as volume strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 34 publications
7
68
0
2
Order By: Relevance
“…yield stress and tensile strength, depend very much on interfacial adhesion (Dányádi et al, 2007a;Dányádi et al, 2007b;Dányádi et al, 2006;Renner et al, 2009). This is demonstrated well by Fig.…”
Section: Propertiessupporting
confidence: 70%
See 2 more Smart Citations
“…yield stress and tensile strength, depend very much on interfacial adhesion (Dányádi et al, 2007a;Dányádi et al, 2007b;Dányádi et al, 2006;Renner et al, 2009). This is demonstrated well by Fig.…”
Section: Propertiessupporting
confidence: 70%
“…Wood fibers reinforce PP considerably, stiffness increases from the initial value of 1.3 GPa to around 4 GPa. Composites without coupling agent and with MAPP have practically the same modulus proving that the strength of interfacial adhesion does not influence stiffness much (Dányádi et al, 2007a;Dányádi et al, 2007b;Renner et al, 2009). On the other hand, the correlation obtained for the composites containing MAEPDM deviates from that of the other two sets of materials indicating a slight degree of embedding in this case.…”
Section: Propertiesmentioning
confidence: 92%
See 1 more Smart Citation
“…The stiffness of the composites is not influenced significantly by the presence of the functionalized polymer [3,17,27], but strength usually increases considerably [2,3,17,19,27,28]. The tensile and flexural strength of polymers usually decreases with increasing filler content in the absence of coupling [2,19,28,31], but the correlation can be turned around and considerable increase can be achieved with the help of functionalized polymers.…”
Section: Introductionmentioning
confidence: 97%
“…In previous papers we presented the effect of various factors on the deformation and failure of wood flour filled PP composites [31,33]. We found that the dominating 5 micromechanical deformation mechanism is debonding in these materials, indeed.…”
Section: Introductionmentioning
confidence: 99%